Functional and biological diversity of foliar spectra in tree canopies throughout the Andes to Amazon region. Issue 1 (18th June 2014) - Asner, Gregory P.; Martin, Roberta E.; Carranza‐Jiménez, Loreli; Sinca, Felipe; Tupayachi, Raul; Anderson, Christopher B.; Martinez, Paola
Summary: Spectral properties of foliage express fundamental chemical interactions of canopies with solar radiation. However, the degree to which leaf spectra track chemical traits across environmental gradients in tropical forests is unknown. We analyzed leaf reflectance and transmittance spectra in 2567 tropical canopy trees comprising 1449 species in 17 forests along a 3400‐m elevation and soil fertility gradient from the Amazonian lowlands to the Andean treeline. We developed quantitative links between 21 leaf traits and 400–2500‐nm spectra, and developed classifications of tree taxa based on spectral traits. Our results reveal enormous inter‐specific variation in spectral and chemical traits among canopy trees of the western Amazon. Chemical traits mediating primary production were tightly linked to elevational changes in foliar spectral signatures. By contrast, defense compounds and rock‐derived nutrients tracked foliar spectral variation with changing soil fertility in the lowlands. Despite the effects of abiotic filtering on mean foliar spectral properties of tree communities, the spectra were dominated by phylogeny within any given community, and spectroscopy accurately classified 85–93% of Amazonian tree species. Our findings quantify how tropical tree canopies interact with sunlight, and indicate how to measure the functional and biological diversity of forests with spectroscopy.